2019
DOI: 10.1002/anie.201905580
|View full text |Cite
|
Sign up to set email alerts
|

Data‐Driven Identification of Hydrogen Sulfide Scavengers

Abstract: Hydrogen sulfide (H 2 S) is an important signaling molecule whose up-and down-regulation have specific biological consequences.A lthough significant advances in H 2 S up-regulation, by the development of H 2 Sd onors,h ave been achieved in recent years,p recise H 2 Sd own-regulation is still challenging.T he lacko fp otent/specific inhibitors for H 2 Sproducing enzymes contributes to this problem. We expect the development of H 2 Ss cavengers is an alternative approach to address this problem. Since chemical s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
22
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 40 publications
0
22
1
Order By: Relevance
“…Interestingly, during the examination of VitB 12 roles, it was found that VitB 12 enhanced ATTM-induced LUAD cell growth ( Supplementary Figure 1), unlike zinc or copper's inhibitory effects. However, both our study and previous reports suggest VitB 12 is a H 2 S scavenger (34,49). In fact, it has been documented that high VitB 12 can raise the risk of lung cancer (17).…”
Section: Discussioncontrasting
confidence: 64%
“…Interestingly, during the examination of VitB 12 roles, it was found that VitB 12 enhanced ATTM-induced LUAD cell growth ( Supplementary Figure 1), unlike zinc or copper's inhibitory effects. However, both our study and previous reports suggest VitB 12 is a H 2 S scavenger (34,49). In fact, it has been documented that high VitB 12 can raise the risk of lung cancer (17).…”
Section: Discussioncontrasting
confidence: 64%
“…In recent years, the studies of H 2 S on HCC tumorigenesis are conflicting, i.e. anti-cancer vs. pro-cancer (Wu et al, 2017;Yang et al, 2019b;Wu et al, 2019). Those studies on H 2 S's anti-HCC activity, we think, are probably due to the generation of sulfane sulfur from Na 2 S/NaHS.…”
Section: Discussionmentioning
confidence: 91%
“…Additionally, some endogenous RSS, like cystine, cysteine, homocysteine, methionine, glutathione, and hydrogen sulfide (H 2 S), are not sulfane sulfur per se, but can be metabolized to produce sulfane sulfur (Jackson et al, 2012). However, the effects of these RSS on cancer therapy including HCC are contradictory, as both anti-cancer (Iciek et al, 2001;Iciek et al, 2012) and pro-cancer (Pan et al, 2014;Zhen et al, 2018;Yang et al, 2019b) activities have been reported, which hinders the sulfurbased HCC therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Nanomaterials with unique chemical and physical properties have wide promising application in catalysis, sensing, photography, optoelectronics, biomedicine, etc 1–6. During the preparation, multiparameters control is the key to achieve specific nanostructures, while a negligible parameter adjustment sometimes leads to fundamentally tremendous change in morphology of nanomaterial (e.g., size, shape, and composition), like the “butterfly effect.”7–10 Electrochemical deposition as a traditional nanomaterial preparation method has been widely employed to fabricate noble metal nanostructures via regulating multiple parameters including deposition time, potential, ion concentration, and temperature 11–13. However, traditional electrodeposition processes for new structure/function exploration are always carried out in large bulk solution system and usually surrounded by trial‐ and error‐based search, brute‐force enumeration, random selection, and intuition‐driven design,14–16 which lead to long research cycle, high reagent consuming/wasting and low efficiency and definitely hinder the fast paced advances in materials science today.…”
Section: Introductionmentioning
confidence: 99%